2009
DOI: 10.1063/1.3246006
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of high-current vacuum arc characteristics under combined action of axial magnetic field and external magnetic field from bus bar

Abstract: In this paper, the two-dimensional high-current vacuum arc (HCVA) model under the combined action of axial magnetic field (AMF) and external magnetic field from bus bar (EMFBB) is established. Based on this model, the influence of AMF and EMFBB on HCVA characteristics can be simulated and analyzed. Simulation results show that the HCVA column will be deflected by the Lorentz force generated by EMFBB and higher arc current. Moreover, the deflection level will be increased with the increase in external EMFBB str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…External magnetic field will affect its characteristics since the ADP can be regarded as a magnetic fluid. Wang et al [80] explored the effects of axial magnetic field (AMF) and external magnetic field from bus bar (EMFBB) on high-current vacuum arc (HCVA) characteristics by modeling a 2D HCVA under the combined action of AMF and EMFBB. The results showed that the Lorentz force produced by EMFBB and higher arc current can deflect HCVA column, and the current on the side near the cathode deflects the Lorentz force more obviously than the current on the side near the anode.…”
Section: Numerical Simulation Of Adp Generatorsmentioning
confidence: 99%
“…External magnetic field will affect its characteristics since the ADP can be regarded as a magnetic fluid. Wang et al [80] explored the effects of axial magnetic field (AMF) and external magnetic field from bus bar (EMFBB) on high-current vacuum arc (HCVA) characteristics by modeling a 2D HCVA under the combined action of AMF and EMFBB. The results showed that the Lorentz force produced by EMFBB and higher arc current can deflect HCVA column, and the current on the side near the cathode deflects the Lorentz force more obviously than the current on the side near the anode.…”
Section: Numerical Simulation Of Adp Generatorsmentioning
confidence: 99%
“…To solve the former equations set (1-7), COMSOL Multiphysics was greatly helpful; some predefined functions were used for better simulation. Boundary conditions were defined as in [13]; more detailed calculations were presented by [14]. In this simulation B y represents AMF which is considered to be uniformly distributed, meaning that the gradient of B y along different directions is zero.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Many researchers conducted modeling and simulation studies on vacuum arcs [20][21][22][23][24][25][26][27][28][29][30][31]. Recently, through the numerical simulation, Wang et al studied the vacuum arc characteristics under the influence of the electrode's self-generated axial magnetic field (AMF) and ETMF [32][33][34][35]. However, the above researchers did not consider both the real AMF and real ETMF in the case of a three-dimensional model, and neither studied how to weaken the influence of the ETMF on vacuum arc by changing the structural parameters.…”
Section: Introductionmentioning
confidence: 99%